e+3e+(-10)=2e+8

Simple and best practice solution for e+3e+(-10)=2e+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for e+3e+(-10)=2e+8 equation:


Simplifying
e + 3e + (-10) = 2e + 8
e + 3e + -10 = 2e + 8

Reorder the terms:
-10 + e + 3e = 2e + 8

Combine like terms: e + 3e = 4e
-10 + 4e = 2e + 8

Reorder the terms:
-10 + 4e = 8 + 2e

Solving
-10 + 4e = 8 + 2e

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-2e' to each side of the equation.
-10 + 4e + -2e = 8 + 2e + -2e

Combine like terms: 4e + -2e = 2e
-10 + 2e = 8 + 2e + -2e

Combine like terms: 2e + -2e = 0
-10 + 2e = 8 + 0
-10 + 2e = 8

Add '10' to each side of the equation.
-10 + 10 + 2e = 8 + 10

Combine like terms: -10 + 10 = 0
0 + 2e = 8 + 10
2e = 8 + 10

Combine like terms: 8 + 10 = 18
2e = 18

Divide each side by '2'.
e = 9

Simplifying
e = 9

See similar equations:

| u-c+d=9 | | 5(-2)+9y=35 | | u-c+d=9forc | | -5+7x=-19 | | A=mn | | 7-1*0+3-3= | | -50-5(-5)= | | 4x^2+6x+4= | | -6x-10=5x+23 | | 5x+9(9+2x)=35 | | Coy^2x-1=0 | | 55x+100-22= | | -7.66+13.2p-2.7p=5.22+11.3p | | 0.7(3x+6)=1.3-(x-3) | | 3y-7+y+3=180 | | 3y-7+y+3=180 | | 3x^2-4x+48=0 | | x^3-3x^2-60x-224=0 | | 80x=480 | | 4x-5=7x+2-3X | | e+2e+(-5)=-11 | | 1x-12=-8(1x-3) | | e^2x-4=.916 | | 2x+x+5=180 | | 4f-5=7f+2-3f | | 116-(6x+8)=6(x+5)+x | | 116-(6x+8)=6(x+5)+x | | 4f-5=7f+2-3f | | -16=4u-8 | | 10d-12=15 | | 6x+6y=156.6 | | 6x+6y=156.6 |

Equations solver categories